La Villa Vieja de Heredia, sus elites políticas y el reformismo borbónico en la Costa Rica del siglo xviii, 1706-1812 - Eduardo MADRIGAL MUÑOZ (Caravelle)
This work aims to return to the study of the foundation and evolution processes of Costa Rica’s Villas of the Central Valley in the 18th century. Previous historians have undertaken the subject, stating that the origin of modern Costa Rica lies in these Villas. However, it seems necessary to review the theme using new theoretical and methodological perspectives, as well as proposing a broadening of the archival research, in order to achieve a deeper comprehension of these processes, unreached until today. Historiography on the subject is analysed and a prosopographical study based on social networks theory of their political authorities is suggested. The work concentrates on Heredia and San José.